Nature as a stakeholder: including nature in corporate governance practices to meet the EU corporate sustainability reporting directive - Tineke Lambooy; Ebba Hooft Toomey; Alexandra Pimor; Daan van Apeldoorn; Lucy Ward; Pooja Sharma; Jacobien Viets; Tessa Van Soest (Mednarodno Inovativno Poslovanje)
This paper provides one of the first reviews of Nature-inclusive corporate governance models, as implemented in the day-to-day practice of ten identified businesses. Two key drivers of the formation of Nature-inclusive governance are increasingly urgent environmental change and the rise of corporate social responsibility reporting mechanisms and laws, notably the EU Corporate Sustainability Reporting Directive (CSRD). The research consists of qualitative analysis of interviews with representatives of companies that have given Nature a governance role. These interviews were accompanied by legal research in several European jurisdictions (the Netherlands, Belgium, and the United Kingdom) to identify additional legal options for incorporating Nature in corporate governance. Based on the findings, a framework of innovative Nature-inclusive governance models was developed and is presented in this paper. It consists of four models: Nature as Inspiration, Nature as Advisor, Nature as Director, and Nature as Shareholder. These models and the underlying framework provide essential context for understanding the changing landscape of corporate governance and meaningful tools for academics, legal and financial consultants, and businesses interested in understanding emerging Nature-inclusive corporate governance models.